Synthesis and In Vitro Pharmacological Evaluation of 5,8-Dideaza Analogs of Methotrexate - Marta Abellán-Flos; Charles Skarbek; Dáire J. Gibbons; Estelle Rascol; Ainhoa García; Raphaël Labruère (Molecules)
This study describes the synthesis of a series of dideaza analogs of methotrexate and their preliminary pharmacological and metabolic evaluation. The 5,8-dideazamethotrexate was efficiently obtained in five steps using a new synthetic route. Oxygenated and thiolated analogs of dideazamethotrexate were prepared following the devised pathway. Their cytotoxicity was studied in the A549 lung cancer cell line, as well as their DHFR dihydrofolate reductase inhibition activity and in vitro metabolism. The two new analogs showed strong activity on cancer cells and the enzymatic target. These compounds were not metabolized, a clear advantage over methotrexate, which is rapidly converted to the toxic metabolite 7-hydroxymethotrexate.